Incidental Detection of Thoracic Ectopic Kidney with Bochdalek Hernia: A Case Report - Alim, Noor E Amrin; Muhtasim, Muhammad Farhan; Persi, Abdullah Al; Khan, Mahjabin Nobi; Hoq, Md Ajijul; Hossain, Mohammad Sazzad; Akhter, Anjuman Ara; Bhattacharjee, Pabitra Kumar (Bangladesh Journal of Nuclear Medicine, 2025)
A thoracic ectopic kidney is the rarest kind of ectopic kidney, occurring in one out of every 15,000 cases. This renal anomaly is frequently diagnosed incidentally. We report a case of a man who had a non-visualized left kidney and later found out to be having a left thoracic kidney associated with a left Bochdalek hernia. Bangladesh J. Nuclear Med. 27(2): 305-309, 2024